HUMAN RESOURCE MANAGEMENT STRATEGIES FOR SUSTAINABLE ORGANIZATIONAL GROWTH - Suprayitno; Supardi (Adisam Publisher, 2024)
The implementation of human resource management techniques for sustainable organizational growth entails managing, developing, and utilizing employee potential to continuously support the attainment of corporate goals. Companies can provide a work environment where employees can grow both emotionally and professionally while effectively addressing new possibilities and challenges in the market by putting into practice human resource management methods that are focused on sustainable organizational growth. One crucial element in promoting long-term organizational growth is the innovative role that HRM strategy plays. Innovation offers answers to a range of problems in the field of human resources, including performance management, employee development, and the hiring and selecting process. Using a literature review methodology, this study thoroughly examines HRM techniques for long-term organizational expansion. The concept of HRM in the context of sustainable organizational growth, the relationship between HRM and organizational strategy, and the function of innovation in HRM strategy for organizational growth are all covered in this study.